Extraction and Evaluation of Lipid Entrapment Ability of Ocimum basilicum L. Seed Mucilage - Nguyen-Le, Duy; Nguyen, Cao-Tri; Ton-That, Quang; Tran, Thuoc Linh; Tran-Van, Hieu (Indian Journal of Pharmaceutical Education and Research, 2021)
Background: Overweight, obesity is a serious health problem worldwide and has been becoming an epidemic recently due to the rapid growth of its prevalence. The consequences of obesity are not only its related diseases such as diabetes and cardio vascular disease, but also the effects on global socio-economic. Aim: In this study, we obtained and evaluated characteristics of Ocimum basilicum L. (OB) seed mucilage which fit for developing a weight control product through several characteristics such as swelling index, stability, toxicity and lipid adsorption/absorption from different sources. All of the statistical analysis was done by Graphpad prism using unpaired t-test. Results: The extraction yield by physical method was 10.17% and the swelling index of dried mucilage was 20.6 times higher than the initial weight. The drying temperature affected only on the mucilage through the increasing of reducing sugars concentration. The OB mucilage showed neither cytotoxicity on NIH-3T3 cells nor chronic/acute toxicity on mice. Last but not least, OB mucilage was able to absorb/adsorb lipid from different lipid sources. Conclusion: OB mucilage was proven to be a high potential source of polysaccharide for developing weight treatment products.
Keywords: High swelling index; Lipid adsorption/absorption; Mucilage characteristics; Ocimum basilicum L.; Obesity